Knowledge, Usage and Perceived Side Effects of Monosodium Glutamate (MSG) among Catering Student at UTHM - Abd Rani, Afif Naim; Tukiran, Nor Anis Intan Aqiah (Online Journal for TVET Practitioners, 2025)
Monosodium glutamate (MSG) is a common flavor enhancer, yet perceptions of its safety remain mixed. This study assessed catering students’ knowledge, usage, and perceived side effects of MSG at Universiti Tun Hussein Onn Malaysia (UTHM). A descriptive, cross-sectional survey was administered to 92 students using a structured questionnaire covering demographics, MSG knowledge, usage patterns, and perceived side effects; descriptive statistics (frequency, percentage, mean, standard deviation) were computed in SPSS version 26.0. Overall, respondents demonstrated a moderate level of knowledge about MSG and a moderate level of usage, while perceived side effects were rated high on average, indicating persistent concerns about adverse effects despite moderate understanding and use. These findings suggest the need for targeted education on evidence-based safety thresholds, labeling literacy, and best-practice application of flavor enhancers in culinary settings. Future research should compare cohorts (e.g., by year of study or exposure to food science coursework) and incorporate inferential analyses to examine associations among knowledge, usage, and perceived side effects.